2021
DOI: 10.1371/journal.pone.0246154
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice towards COVID-19 pandemic and its prevalence among hospital visitors at Ataye district hospital, Northeast Ethiopia

Abstract: Background Coronavirus disease 19 (COVID-19) is currently a global health threat and public health emergency of international concern. Africa is the last continent to be hit by this pandemic and the population is still prone to misconceptions and may not take it seriously. In developing countries including Ethiopia, where trained human resources and equipment for the treatment of COVID-19 are scarce, working on prevention of the viral spread should be a priority as a feasible intervention strategy. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
(48 reference statements)
7
25
1
Order By: Relevance
“…Literature on behavioural response to Covid-19 is fast emerging [13][14][15][16][17][18]. The limitations highlighted in the context of the pandemic literature prior to Covid-19 holds true for the more recent studies as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature on behavioural response to Covid-19 is fast emerging [13][14][15][16][17][18]. The limitations highlighted in the context of the pandemic literature prior to Covid-19 holds true for the more recent studies as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, visitors of healthcare facilities are one of the victim groups of population for COVID-19 due to close contact with suspected and confirmed cases of the disease. Occupation, sex, age, family size, marital status, residence, average monthly income, and alcohol consumption were some of the factors affecting knowledge, attitude and practices of COVID-19 [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even though they have inadequate knowledge, the proportion of the low level of knowledge were decreased. The reason might be since the current study was conducted after most of the population obtained information about the disease in several ways (Gebretsadik et al, 2021). Gebretsadik et al (2021) and Yoseph et al (2021) also stated that it might be due to the study participants getting access to the internet service, which helped them find information about the disease from several sources.…”
Section: Knowledge Toward Covid-19 Preventionmentioning
confidence: 99%
“…The reason might be since the current study was conducted after most of the population obtained information about the disease in several ways (Gebretsadik et al, 2021). Gebretsadik et al (2021) and Yoseph et al (2021) also stated that it might be due to the study participants getting access to the internet service, which helped them find information about the disease from several sources. Other studies showed that the excellent knowledge of COVID-19 might be due to the study respondents live in urban residence with higher education degree (Gao et al, 2020;Mohamed et al, 2021).…”
Section: Knowledge Toward Covid-19 Preventionmentioning
confidence: 99%